Methylmercury carbon isotope fractionation during biotic methylation by the bacterial BerOc1 strain - Luisa M. Malberti-Quintero; Jin-Ping Xue; Remy Guyoneaud; Alina Kleindienst; Christelle Lagane; Laure Laffont; Jeroen E. Sonke; Zoyne Pedrero; Emmanuel Tessier; David Amouroux; David Point (npj Clean Water)
Abstract Biotic methylation of inorganic mercury (iHg) in aquatic systems is largely driven by microorganisms such as sulfate-reducing bacteria (SRB). Using the SRB model strain Pseudodesulfovibrio hydrargyri BerOc1 we investigated biotic iHg methylation aiming to assess the rates of mono-methylmercury (CH3Hg) production and to characterize the carbon (C) isotopic signatures (δ13C) of the CH3Hg product. BiogenicCH3Hg exhibited δ13C values averaging −23.1 ± 2.0‰, representing a 13C-depletion of 14.4‰ compared to the pyruvate carbon source used for the growing of the strain and a 9‰ depletion relative to the microbial biomass. The maximum methylation yield observed in our samples was around 15% of the available iHg and a constant C isotope fractionation was detected over time. We propose that the methyl group is metabolically transferred from the carbon sources to cobalamin in the HgcA protein and subsequently to inorganic mercury (iHg), leading to consistent light C isotope enriched CH3Hg signatures.